Biochemical and Transcriptional Regulation of Membrane Lipid Metabolism in Maize Leaves under Low Temperature - Gu, Yingnan; He, Lin; Zhao, Changjiang; Wang, Feng; Yan, Bowei; Gao, Yuqiao; Li, Zuotong; Yang, Kejun; Xu, Jingyu (Frontiers in Plant Science, 2017)
Membrane lipid modulation is one of the major strategies plants have developed for cold acclimation. In this study, a combined lipidomic and transcriptomic analysis was conducted, and the changes in glycerolipids contents and species, and transcriptional regulation of lipid metabolism in maize leaves under low temperature treatment (5°C) were investigated. The lipidomic analysis showed an increase in the phospholipid phosphatidic acid (PA) and a decrease in phosphatidylcholine (PC). And an increase in digalactosyldiacylglycerol (DGDG) and a decrease in monogalactosyldiacylglycerol (MGDG) of the galactolipid class. The results implied an enhanced turnover of PC to PA to serve as precursors for galactolipid synthesis under following low temperature treatment. The analysis of changes in abundance of various lipid molecular species suggested major alterations of different pathways of plastidic lipids synthesis in maize under cold treatment. The synchronous transcriptomic analysis revealed that genes involved in phospholipid and galactolipid synthesis pathways were significantly up-regulated, and a comprehensive gene-metabolite network was generated illustrating activated membrane lipids adjustment in maize leaves following cold treatment. This study will help to understand the regulation of glycerolipids metabolism at both biochemical and molecular biological levels in 18:3 plants and to decipher the roles played by lipid remodeling in cold response in major field crop maize.